A systematic literature review in gamification implementation and game elements in Malaysia education - Mazlan, Azlimi; Ahmad, Ibrahim; Salam, Sazilah (2023)
In recent years, Gamification has increased interest in both industries and academia. Gamification takes most of the game elements to be applied in the teaching and learning process to see student behaviors. However, Gamification focuses mainly on game-based learning and serious game. Many gamification approaches have been implemented in public schools compared to higher education institutions. Gamification is also used in businesses. This paper aims to explore the gamification approach in Malaysia through a systematic literature review and discuss the game elements used in the gamification context. The finding shows that there is a gamification context in higher education institutions in Malaysia, and the game elements used in gamification are points, badges, leaderboards, and many more.